Challenges and barriers to noncommunicable disease management at community health centers in south Sumatera province, Indonesia: A qualitative study - Muhammad Agung Akbar; Junaiti Sahar; Etty Rekawati; Rayu Ayu Dewi Sartika (Nursing Practice Today)
Background & Aim: Noncommunicable diseases (NCDs) are the leading cause of morbidity and mortality worldwide, heavily impacting low and middle-income countries like Indonesia. Community Health Centers (CHCs) play a critical role in providing healthcare, including NCD management, but they face significant challenges. This study explores the challenges and barriers to NCD management at CHCs in South Sumatra Province, Indonesia. Methods & Materials: To gain an in-depth understanding of healthcare workers’ management of NCDs, an exploratory content analysis approach was employed. Data were collected through semi-structured interviews with 12 health workers, including nurses, doctors, midwives, and public health workers. Content analysis was used for data analysis. Results: The content analysis identified five themes: Resource constraints in primary healthcare, lack of effective interprofessional collaboration, social and cultural issues; work area coverage, and government policy and support. Conclusion: These findings highlight the complex challenges faced by CHCs. Addressing them requires a comprehensive strategy to enhance NCD care and primary healthcare services. Policymakers and health system managers can use these insights to develop targeted interventions. Further research is recommended to assess the effectiveness of specific strategies in overcoming these barriers in low-resource settings.